Mycobacterium leprae Is Naturally Resistant to PA-824 - Manjunatha, Ujjini H. (American Society for Microbiology, 2006)
Leprosy responds very slowly to the current multidrug therapy, and hence there is a need for novel drugs with potent bactericidal activity. PA-824 is a 4-nitroimidazo-oxazine that is currently undergoing phase I clinical trials for the treatment of tuberculosis. The activity of PA-824 against Mycobacterium leprae was tested and compared with that of rifampin in axenic cultures, macrophages, and two different animal models. Our results conclusively demonstrate that PA-824 has no effect on the viability of M. leprae in all three models, consistent with the lack of the nitroimidazo-oxazine-specific nitroreductase, encoded by Rv3547 in the M. leprae genome, which is essential for activation of this molecule.